Prolonged Grief Disorder in a Diverse College Student Sample - Glickman, Kim (Frontiers in Psychology, 2021)
Objective: The purpose of this study was to explore the rate of prolonged grief disorder (PGD) and associated factors in a large sample of diverse college students. Sources of grief support and perceived helpfulness of support were also examined. Method: An online survey was administered to bereaved students at three colleges at the City University of New York. PGD, measured by the Inventory of Complicated Grief was the primary outcome. Chi-squared and t-tests were used to assess the association between PGD and associated factors. Results: A total of n=899 participants completed the ICG based on a significant death loss => 12 months. An estimated 13.4% (n=120/899) met criteria for PGD. The rate of PGD was associated with race, history of anxiety or depression, trauma other than the death, insecure attachment style, kinship to the deceased, closeness to the deceased, cause of death and sudden/unexpected death. The majority of students sought grief support from a friend or family member. Conclusion: The rate of PGD in this sample of college students is similar to that of adults and most prevalent for students of color. Identification of those most at risk is critical to referring these students to effective treatments.